"Names doing rounds": On brands in the bazaar economy. (May 2022) - Deka, Maitrayee; Arvidsson, Adam
This article draws on fieldwork form Delhi's garment and electronics bazaars to articulate an alternative perspective on the role of brands in the global bazaar economy. Knockoffs and counterfeit brands have mostly been viewed as problematic manifestations of counterfeiting and piracy, or framed in terms of authenticity or marginal practices of imitation. In this article, we suggest that bazaar brands also function as central to a growing popular innovation system able to provide material goods as well as immaterial experiences to the world's poorer consumers in ways that stay in close contacts with the mediated fluctuations of popular affects. Bazaar brands develop a unique relationship with consumers based on an ability to seize the moment rather than the creation of enduring loyalties. We suggest that bazaar brands can be understood as central to an emerging postcapitalist consumer economy that has been substantially empowered by the spread of digital technologies.